Assessment of Melatonergics in Prevention of Delirium: A Systematic Review and Meta-Analysis - Zhu, Yibing; Jiang, Zhiming; Huang, Huibin; Li, Wen; Ren, Chao; Yao, Renqi; Wang, Yang; Yao, Yongming; Li, Wei; Du, Bin; Xi, Xiuming (Frontiers in Neurology, 2020)
Background: Delirium is a commonly found comorbidity in hospitalized patients and associated with adverse outcomes. Melatonin is an endogenous hormone that exerts multiple biological effects, mainly in regulating diurnal rhythms, and in inflammatory process and immune responses. We aimed to assess the efficacy of exogenous melatonergics in the prevention of delirium. Methods: We conducted a search to identify relevant randomized controlled studies (RCTs) in the PubMed, Cochrane Library, and Embase databases that had been published up to December 2019. Hospitalized adult patients administered melatonergics were included. The primary outcome measure was the incidence of delirium. The secondary outcome measure was the length of stay in intensive care unit (ICU-LOS). The pooled effects were analyzed as the risk ratio (RR) for delirium incidence, weighted mean difference (WMD) for ICU-LOS, and 95% confidence intervals (CIs). Results: Nine RCTs with 1,210 patients were included. The forest plots showed that melatonergics were associated with a decreasing incidence of delirium (RR 0.51, 95% CI 0.30 to 0.85, I² 70%, p 0.01). There was no significant difference in ICU-LOS (WMD -0.08, 95% CI -0.19 to 0.03, I² 0, p 0.17). Conclusion: Administration of exogenous melatonergics to hospitalized patients seems to be associated with a decreasing incidence of delirium. PROSPERO registration number: CRD42019138863.